GURE ERTILARIAK, Montes Iturrioz Gaspar, Bidasoako Alderdi Ederraren Pintatzaillea - Alzola, N. (EGAN, 2021)
N. ALZOLA: GURE ERTILARIAK, Montes Iturrioz Gaspar, Bidasoako Alderdi Ederraren Pintatzaillea